Some applications of minimal open sets - Fumie Nakaoka; Nobuyuki Oda (International Journal of Mathematics and Mathematical Sciences)
We characterize minimal open sets in topological spaces. We show that any nonempty subset of a minimal open set is pre-open. As an application of a theory of minimal open sets, we obtain a sufficient condition for a locally finite space to be a pre-Hausdorff space.